Multivariate analysis of the exposure and hazard of ceria nanomaterials in indoor aquatic mesocosms. Issue 6 (30th April 2020) - Nassar, Mohammad; Auffan, Mélanie; Santaella, Catherine; Masion, Armand; Rose, Jérôme
Abstract : Associating mesocosm experimentations with multivariate analyses to identify the parameters governing the behavior and impact of nanomaterials on aquatic ecosystems. Abstract : The vast diversity of applications using nanomaterials and enhanced physicochemical properties at the nanoscale have raised questions concerning their potential environmental risks. Assessing the risk of nanomaterials in a real ecosystem is extremely challenging because of the system complexity and the relevant environmental doses tested. To provide ultimate interpretations about nanomaterial risk assessment, we combined ceria nanomaterial behavior, fate and impact analysis within indoor aquatic mesocosms with multivariate analysis. Principal Component Analysis (PCA) showed that the exposure scenario to CeO2 nanoparticles (NPs) constitutes the main parameter to consider while investigating the risk for a given ecosystem. Moreover, following single pulse dosing of CeO2 NPs, the global response of the pond ecosystem was time dependent. However, multiple dosing contamination failed to significantly perturb the system over time. Finally, the NP surface coating was found to play a secondary role and to affect the global response of the pond ecosystem in the short term only.